A maqashid sharia perspective on thrifting: Case study of imported secondhand clothing at Sederek Store Yogyakarta - Alafianta, Novan Fatchu; Fadhilah, Zahro Inayatul; Dinia, Nazia (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
The thrifting trend is gaining popularity in Indonesia and is favored by many consumers, mainly due to the rise of the “hype-thrift” phenomenon in the fashion industry. According to a Goodstats survey, 49.4% of respondents reported purchasing secondhand clothing through thrifting. However, the Indonesian government prohibits the import of used clothing under MOT Regulation No. 51/M-DAG/PER/7/2015, as it contradicts trade policies and poses risks to the domestic textile industry. Despite this regulation, the thrifting practice continues to grow rapidly and is challenging to control. This research aims to analyze the practice of buying and selling imported secondhand clothing at Sederek Store Yogyakarta from the perspective of Maqashid Sharia. Employing a qualitative-descriptive approach, data were collected through observation, interviews, and documentation. The data were analyzed using Miles and Huberman’s model, consisting of data reduction, presentation, and conclusion drawing. Findings reveal that Sederek Store operates physically and digitally through Instagram and TikTok, offering cleaned and curated secondhand clothing. Although the business does not fully align with the Maqashid Sharia principle of property preservation (hifdz al-mal) due to its potential impact on the local economy, it supports four other objectives: protecting religion, life, intellect, and progeny. The study recommends that Sederek Store prioritize hygiene and transparency while promoting Islamic values in commerce. Additionally, consumers should exercise critical awareness when purchasing and the government is urged to enforce regulations while accommodating the interests of all stakeholders involved.